Efficacy of insecticides on black-headed stem borer, Chilo polychrysus walker (Lepidoptera: Pyralidae) in glasshouse condition - Nur Atiqah Mohd Khari; Suhaila Ab Hamid (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Three groups of insecticides; two from diamide and one from phenylpyrazole exemplified by chlorantraniliprole, flubendiamide, and fipronil, respectively, are the most widely used conventional insecticides in Malaysia to control several pests of lepidopterans in rice, including black-headed stem borer, Chilo polychrysus. However, the development of insecticide resistance in the rice stem borer has been raised up in many other countries. Therefore, this study aims to verify the efficacy of fipronil, flubendiamide and chlorantraniliprole to the susceptible colony of C. polychrysus as the initiative for the resistance monitoring. A seedling dip bioassay method was adopted to compare the efficacy and lethal concentration (LC50) of the three conventional insecticides. The insecticide efficacy (Et) was determined from the mortality percentage of C. polychrysus. The initial efficacy (at 24 hours) of fipronil, flubendiamide and chlorantraniliprole were 87.5%, 15.8% and 21.7% respectively. The effectiveness of the insecticides is determined by the mortality percentage or the final efficacy (Et). The final efficacy of fipronil was recorded at 72 hours of observation, followed by flubendiamide (96 hours) and chlorantraniliprole (120 hours). The lethality index (LI) of fipronil was the highest, (96.7%) that caused rapid effect to the rice stem borer. Result of toxicity effect showed that LC50 for fipronil was the most effective against C. polychrysus with 16.12 mg/L followed by chlorantraniliprole (43.25 mg/L) and flubendiamide (76.43 mg/L).The LC50 value of fipronil was significantly different to flubendiamide but not to chlorantraniliprole. Thus, fipronil is the most toxic and most effective insecticide to control C. polychrysus in glasshouse.